Cytochrome P450 1A1 Gene Polymorphisms and Endometrial Cancer Risk: A Meta-Analysis. Issue 2 (1st January 2011) - Sergentanis, Theodoros N.; Economopoulos, Konstantinos P.; Choussein, Souzana; Vlahos, Nikos F.
Abstract : Introduction: This meta-analysis aims to examine whether the genotype status of Msp1, Ile462Val, and Thr461Asn polymorphisms in cytochrome P450 1A1 (CYP1A1) is associated with endometrial cancer risk. Methods: Eligible case-control studies were identified through search in MEDLINE (end of search: August 2010). Pooled odds ratios (ORs) were appropriately derived from fixed-effects or random-effects models. Results: Concerning Msp I polymorphism, 8 studies were eligible (1456 cases and 2371 controls); 9 studies were eligible (1889 cases and 3662 controls) for Ile462Val and 6 studies were eligible (1272 cases and 2122 controls) for Thr461Asn. Msp I polymorphism was not associated with endometrial cancer risk (for heterozygous TC vs TT carriers: OR = 0.83, 95% confidence interval [CI], 0.59-1.15, random effects; for homozygous CC vs TT carriers: OR = 1.00, 95% CI, 0.55-1.82, fixed effects). Similarly, Ile462Val polymorphism was not associated with endometrial cancer risk (for heterozygous Ile/Val vs Ile/Ile carriers: OR = 1.27, 95% CI, 0.78-2.06, random effects; for homozygous Val/Val vs Ile/Ile carriers: OR = 1.16, 95% CI, 0.48-2.81, fixed effects). Accordingly, Thr461Asn status was not significantly associated with endometrial cancer risk. The same results were reproduced in Caucasians. Conclusions: The 3 examined CYP1A1 genotype polymorphisms do not seem to confer any additional risk for endometrial cancer in Caucasians. Accumulation of further data seems mandatory for future race-specific analyses.